2000
DOI: 10.1038/labinvest.3780090
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis F508del Patients Have Apically Localized CFTR in a Reduced Number of Airway Cells

Abstract: SUMMARY:Present state of knowledge, mostly based on heterologous expression studies, indicates that the cystic fibrosis transmembrane conductance regulator (CFTR) protein bearing the F508del mutation is misprocessed and mislocalized in the cytoplasm, unable to reach the cell surface. Recently, however, it was described that protein levels and localization are similar between F508del and wild-type CFTR in airway and intestinal tissues, but not in the sweat glands. In this study, we used immunocytochemistry with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 67 publications
11
94
2
Order By: Relevance
“…CFTR protein, as detected by immunolocalization, was first reported in a few unidentified columnar cells within the superficial epithelium (Engelhardt et al, 1992(Engelhardt et al, , 1994 and more recently in a restricted population of columnar cells (Penque et al, 2000;Carvalho-Oliveira et al, 2004). We identified the ciliated cell as the only cell type expressing CFTR in nasal, bronchial, and proximal bronchiolar surface epithelia by high resolution LCM and coimmunostaining with antibodies against cellular markers (e.g., tubulin).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…CFTR protein, as detected by immunolocalization, was first reported in a few unidentified columnar cells within the superficial epithelium (Engelhardt et al, 1992(Engelhardt et al, , 1994 and more recently in a restricted population of columnar cells (Penque et al, 2000;Carvalho-Oliveira et al, 2004). We identified the ciliated cell as the only cell type expressing CFTR in nasal, bronchial, and proximal bronchiolar surface epithelia by high resolution LCM and coimmunostaining with antibodies against cellular markers (e.g., tubulin).…”
Section: Discussionmentioning
confidence: 95%
“…(Engelhardt et al, 1992(Engelhardt et al, , 1194Puchelle et al, 1992;Kalin et al, 1999;Penque et al, 2000). With the availability of very sensitive anti-CFTR mAbs (Mall et al, 2004) and LCM technologies, we initiated a comprehensive study to explore two major issues controversial in CF research: 1) the cell type specific localization of CFTR in the normal lung; and 2) the localization of ⌬F508 CFTR in native airway epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to wt and F508del/F508del cells, in which the CFTR protein could be detected at the apical membrane (Figure 3a), apical CFTR staining was significantly reduced in nasal epithelial cells derived from F508del/3905insT compoundheterozygous patients (Figure 3c; Table 1 Effect of CFTR 3905insT at mRNA and protein level J Sanz et al number of cells from F508del homozygous patients have apically localized CFTR (Figure 3b). 21,36,37 Recent studies indicated that the CFTR C-terminus is not required for the biosynthesis and plasma membrane targeting of CFTR, but indispensable for maintaining the stability of the protein. 38 Benharouga et al 39 could also show that an ERAD-similar mechanism involving the proteasome-ubiquitin pathway may be responsible for the faster turnover and the short residence time at the apical membrane of truncated CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…The most common mutation in CF is the deletion of a phenylalanine residue at position 508 (F508) that causes improper folding of the CFTR protein, resulting in its retention in the endoplasmic reticulum and proteosomal degradation of the majority of the newly synthesized CFTR proteins (Cheng et al, 1990;Kartner et al, 1992;Penque et al, 2000). However, part of the F508-CFTR protein can still mature and reach the cell membrane where it retains some chloride channel function (Bronsveld et al, 2000;Penque et al, 2000;Kopito, 1999).any efforts on CF research are devoted to attempt to rescueF508-CFTR defective trafficking to restore normal epithelial function.…”
Section: Rescue Of F508-cftr Maturation and Membrane Stabilitymentioning
confidence: 99%